Ethanol Extract Of Centella Asiatica (L.) Urban Leaves Effectively Inhibit Streptococcus pyogenes and Pseudomonas aeruginosa by Invitro Test - Dini Aulia Azmi; Nurlailah Nurlailah; Ratih Dewi Dwiyanti (Baiman Bauntung Batuah Center, 2020)
Streptococcus pyogenes and Pseudomonas aeruginosa are some of the causes of infectious diseases. Centella asiatica (L.) Urban has many benefits for humans, including overcoming fever, anti-bacterial, and anti-inflammatory. This study aims to determine the inhibition of Centella asiatica (L.) Urban leaves ethanol extract on the growth of Streptococcus pyogenes and Pseudomonas aeruginosa. This research is the initial stage of the development of herbal medicines to treat Streptococcus pyogenes and Pseudomonas aeruginosa infections. The independent variable was the concentration of ethanol extract of Centella asiatica (L.) Urban leaves and the dependent variable was the growth of Streptococcus pyogenes and Pseudomonas aeruginosa. The anti-bacterial activity test was carried out by the liquid dilution method. The concentrations used are 20%, 40%, 60%, 80%. 100% The results showed that the minimum inhibitory concentration (MIC) against Streptococcus pyogenes: 40% and Pseudomonas aeruginosa: 40%. Minimum bactericidal concentration (MBC) results for Streptococcus pyogenes: 60% and Pseudomonas aeruginosa: 60%. So it can be concluded that there is inhibition of the ethanol extract of Centella asiatica (L.) Urban leaves on the growth of Streptococcus pyogenes and Pseudomonas aeruginosa. Centella Asiatica (L.) Urban extract has potential as herbal medicine against bacterial infections but requires further research to determine its effect in vivo.